Effects of LaNiO3 Seed Layer on the Microstructure and Electrical Properties of Ferroelectric BZT/PZT/BZT Thin Films - Ruan, Jinyu; Yin, Chao; Zhang, Tiandong; Pan, Hao (Frontiers in Materials, 2021)
Ferroelectric multilayer films attract great attention for a wide variation of applications. The synergistic effect by combining different functional layers induces distinctive electrical properties. In this study, ferroelectric BaZr0.2Ti0.8O3/PbZr0.52Ti0.48O3/BaZr0.2Ti0.8O3 (BZT/PZT/BZT) multilayer thin films are designed and fabricated by using the magnetron sputtering method, and a LaNiO3 (LNO) seed layer is introduced. The microstructures and electrical properties of the BZT/PZT/BZT films with and without the LNO seed layer are systematically studied. The results show that the BZT/PZT/BZT/LNO thin film exhibits much lower surface roughness and a preferred (100)-orientation growth, with the growth template and tensile stress provided by the LNO layer. Moreover, an enhanced dielectric constant, decreased dielectric loss, and improved ferroelectric properties are achieved in BZT/PZT/BZT/LNO thin films. This work reveals that the seed layer can play an important role in improving the microstructure and properties of ferroelectric multilayer films.